2009
DOI: 10.5194/angeo-27-933-2009
|View full text |Cite
|
Sign up to set email alerts
|

Naturally enhanced ion-line spectra around the equatorial 150-km region

Abstract: Abstract. For many years strong radar echoes coming from 140-170 km altitudes at low latitudes have been associated to the existence of field-aligned irregularities (FAIs) (the so called 150-km echoes). In this work, we present frequency spectra as well as angular distribution of 150-km echoes. When the 150-km region is observed with beams perpendicular to the magnetic field (B) the observed radar spectra are very narrow with spectral widths between 3-12 m/s. On the other hand, when few-degrees off-perpendicul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(55 citation statements)
references
References 35 publications
3
52
0
Order By: Relevance
“…The off-perpendicular echoes were found to be weaker (by 20-30 dB), and Doppler spectra were broader (as high as 1,000 m/s) than their perpendicular counterpart (e.g., Chau et al, 2009). The perpendicular echoes have narrow spectral features (<15 m/s) and can be as strong as 50 dB above noise.…”
Section: Introductionmentioning
confidence: 92%
“…The off-perpendicular echoes were found to be weaker (by 20-30 dB), and Doppler spectra were broader (as high as 1,000 m/s) than their perpendicular counterpart (e.g., Chau et al, 2009). The perpendicular echoes have narrow spectral features (<15 m/s) and can be as strong as 50 dB above noise.…”
Section: Introductionmentioning
confidence: 92%
“…A great deal of effort has been expended to explain these echoes, but the explanation remains elusive. Sample publications include Chau et al (2009), Chau (2004, Chau and Kudeki (2006b), Choudhary et al (2004), Ecklund (2007, 2008), Nicolls et al (2009), Patra and, Patra et al (2008), and references therein.…”
Section: Ionospheric and Plasma Studiesmentioning
confidence: 98%
“…We must clarify that the comparisons made in this paper refer to Jicamarca observations made with the JULIA radar mode, with antenna beams pointing perpendicular to the magnetic field. New offperpendicular observations made at Jicamarca (Chau, 2004;Chau et al, 2009) also show echoes around 150-km altitude with spectra as wide as the ion line of the incoherent scatter spectrum (spectral width larger than 1000 m s −1 ). Finally, Patra and Rao (2006) also found that most spectral widths of off-equatorial 150-km echoes fall within 2 and 8 m s −1 with a maximum occurrence around 4 m s −1 .…”
Section: On the Spectral Characteristics Of The Observed Echoesmentioning
confidence: 99%
“…Future work includes a more detailed analysis of the changes in echo intensity as a function of season and solar flux and how this variability relates to the new findings of Chau et al (2009). Their results indicates that some of 150-km echoes might not be produced by field-aligned irregularities, but by naturally enhanced ion acoustic waves.…”
Section: Summary and Final Remarksmentioning
confidence: 99%
See 1 more Smart Citation